In vivo real-time visualization of mesenchymal stem cells tropism for cutaneous regeneration using NIR-II fluorescence imaging. (June 2015) - Chen, Guangcun; Tian, Fei; Li, Chunyan; Zhang, Yejun; Weng, Zhen; Zhang, Yan; Peng, Rui; Wang, Qiangbin
Abstract: Mesenchymal stem cells (MSCs) have shown great potential for cutaneous wound regeneration in clinical practice. However, the in vivo homing behavior of intravenously transplanted MSCs to the wounds is still poorly understood. In this work, fluorescence imaging with Ag2 S quantum dots (QDs) in the second near-infrared (NIR-II) window was performed to visualize the dynamic homing behavior of transplanted human mesenchymal stem cells (hMSCs) to a cutaneous wound in mice. Benefiting from the desirable spatial and temporal resolution of Ag2 S QDs-based NIR-II imaging, for the first time, the migration of hMSCs to the wound was dynamically visualized in vivo . By transplanting a blank collagen scaffold in the wound to help the healing, it was found that hMSCs were slowly recruited at the wound after intravenous injection and were predominantly accumulated around the edge of wound. This resulted in poor healing effects in terms of slow wound closure and thin thickness of the regenerated skin. In contrast, for the wound treated by the collagen scaffold loaded with stromal cell derived factor-1α (SDF-1α), more hMSCs were recruited at the wound within a much shorter time and were homogenously distributed across the whole wound area, which enhances the re-epithelialization, the neovascularization, and accelerates the wound healing.